Pengembangan Model Pembelajaran Sentra dan Lingkaran Berbasis Pendidikan Inklusi Untuk Taman Kanak-kanak (TK) - Anindya Purnama; M. Imron Abadi (FKIP Unirow Tuban, 2019)
This study aims to develop a center and circle learning model based on inclusive education in the form of learning modules that can be applied by teachers in kindergarten. This research was conducted to overcome the problems that arise, namely misinterpretation (wrong perception) towards the implementation of inclusive education. Therefore, a development of learning models is needed so that the goals of inclusive education can be achieved. Development of this learning model uses steps proposed by Borg & Gall. The research subjects were 5 kindergartens with 30 teachers as respondents. The instrument of data collection is an observation sheet that includes four dimensions, namely the feasibility of content, language, presentation, and graphics. Furthermore, the data analysis technique was obtained from the calculation of the percentage of the score of the observation sheet which then the results of these percentages were categorized based on criteria namely very weak, weak, sufficient, strong, and very strong. Based on the results of the analysis obtained content eligibility data of 70.8% with a strong category, language validation of 75.6% with a strong category, for presentation validation of 72.8% with a strong category, while for graphic validation is 76.4% with a strong category. This means that learning modules designed for center learning and inclusive education-based circles are classified as good / decent learning tools.